The Collective Subject Discourse: analysis of the student perception about the teaching-learning process in the context of the Covid-19 Pandemic (Research, Society and Development, 2021)
The Covid-19 pandemic has imposed transformations on the teaching-learning process at all stages of formal education. So quickly and without precedent, that academic institutions have sought to resignify themselves. The purpose of this article is to present the challenges and possibilities of education in the context of the pandemic, based on the perceptions of students in the discipline of "Psychology and Development of Learning in Adolescence", offer in the undergraduate courses of the Federal University of Ceará (UFC), Fortaleza campuses (CE), raising dialogues and reflections on the remote teaching-learning process, critical/reflective curriculum theorization, problematizing and interdisciplinary training, using as reference the contributions of Freire (1987), Pimenta (1999) and Silva (2005). Considering the reinvention of the program and the specificities of the discipline, we took as a research instrument the application of an individual questionnaire, in whose analysis we used the Collective Subject Discourse method (Lefèvre, Marques, & Lefèvre, 2003). We understand that the present study showed the importance of considering cognitive, emotional and cultural aspects, with the purpose of rethinking what has already been thought, aiming to potentiate the strength of the educational process in the formation of students in the construction of a critical and autonomous citizenship, with the ability to live and live in a world in constant change with more humanity.